Determinantes do sucesso em processo eleitoral: um estudo empírico nas eleições de 2002 nas regiões nordeste e sul do brasil - Monteiro, Vitor Borges (2005)
The purpose of this study is to verify if the regional differences cause distinct results through the electoral sucess. The raised hypothesis shows that the electorate composition is different when compared with percentual of voters who follow politics and personal convinctions or even sporadically decide their vote, this because of regional characteristics. After estimate the probability of being elect using the Econometric Logit Model, the results show the impact of spending on election campaign on the likelihood of success is greater for the Northeast region, owing to the fact they have more volatile electors. The explicative variables used were: donations declared together to the TSE; Reelection; index of Space concentration of the vote and index of vote dispersion. Finally, if the campaign finance became public as has been suggested by the Public Reform , the resourses distribution should be done considering these regional differences, because the campaign resourses impact on the electors will be completelly different from region to region.